Thermoplastic carboxyl starch-based hot melt adhesive with intrinsic antibacterial and ester exchange characteristics as well as preparation and application of thermoplastic carboxyl starch-based hot melt adhesive
By chelating the combination of thermoplastic carboxylate starch, ethylene-vinyl acetate copolymer and tackifier, combined with metal salt-catalyzed transesterification reaction, the thermoplastic starch-based hot melt adhesive is solved. The poor permeability and insufficient antibacterial properties of thermoplastic starch-based hot melt adhesive at the bonding interface are solved. Problem, high bonding strength and excellent antibacterial properties are achieved, broadening the use scenarios and improving the performance of hot melt adhesives.
Patent Information
- Application Number
- CN202411359199.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The existing thermoplastic starch-based hot melt adhesives have poor permeability at the bonding interface, poor bonding strength, and limited improvement in antibacterial properties of the added filler, which limits the improvement of the performance of the hot melt adhesive.
Using chelating complex thermoplastic carboxylic starch as the matrix, combining ethylene-vinyl acetate copolymer and tackifier, the ester exchange characteristics are catalyzed by metal salt, which improves the affinity and antibacteriality with metals, and granulation through extrusion and granulation. Hot melt adhesive is prepared by intensive blending process.
It achieves high bonding strength, excellent antibacterial properties and interface permeability, broadens the use scenarios of hot melt adhesives, extends the service life, and improves the adhesive performance with metal substrates.
Smart Images

Figure CN119286429A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hot melt adhesives, and in particular relates to a thermoplastic carboxyl starch-based hot melt adhesive with intrinsic antibacterial and transesterification characteristics, and a preparation method and application thereof. Background Art
[0002] Starch has a long history as an adhesive material, but the strong hydrogen bonding force between ordinary starch molecules makes it difficult to use it directly as an adhesive. Thermoplastic starch obtained after plasticizer and thermoplastic processing has good fluidity and adhesion. It is used with other natural materials, such as rosin resin and other tackifiers to prepare TPS-based hot melt adhesives, and is widely used as a substitute for traditional hot melt adhesives such as polyolefins, polyurethanes, and polyesters. However, due to the rigidity of the higher molecular weight native starch, the permeability to the bonding interface is poor, resulting in less than ideal bonding strength.
[0003] CN104312482B discloses a preparation technology of rosin / starch-based biodegradable hot melt adhesive. By high-temperature mixing of thermoplastic starch particles, rosin, polyols, catalysts and antioxidants, the resulting hot melt adhesive meets the technical standard requirements of common commercial hot melt adhesives. CN114381218A acidifies and degrades TPS with organic acid, regulates the molecular weight and viscoelasticity of TPS hot melt adhesive, and further blends it with matrix resin, tackifier and filler to obtain TPS-based hot melt adhesive with high metal bonding strength. On this basis, CN117165218A further obtains antibacterial TPS-based hot melt adhesive with high matrix strength by adding antibacterial fillers, and the copper sheet lap bonding strength can reach 3.5MPa.
[0004] However, the antibacterial properties of hot melt adhesives can only be improved by adding fillers, which is usually limited by the dispersion of fillers in the matrix. In addition, the bonding performance of thermoplastic starch-based hot melt adhesives alone is poor, and they need to be compounded with traditional hot melt adhesives such as EVA. The above problems limit the improvement of hot melt adhesive performance. Therefore, the improvement of the performance of existing thermoplastic starch-based hot melt adhesives needs to overcome the problem of interface compatibility with the matrix resin. Summary of the invention
[0005] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary object of the present invention is to provide a thermoplastic carboxyl starch-based hot melt adhesive with intrinsic antibacterial and transesterification characteristics.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned thermoplastic carboxyl starch-based hot melt adhesive.
[0007] Another object of the present invention is to provide an application of the above-mentioned thermoplastic carboxyl starch-based hot melt adhesive.
[0008] The purpose of the present invention is achieved through the following solutions:
[0009] A thermoplastic carboxyl starch-based hot melt adhesive with intrinsic antibacterial and transesterification characteristics is prepared by comprising the following components in parts by weight: 40-80 parts of chelated coordinated thermoplastic carboxyl starch, 10-30 parts of ethylene-vinyl acetate copolymer, 10-30 parts of tackifier, and 0.2-0.4 parts of antioxidant.
[0010] Furthermore, the chelated coordinated thermoplastic carboxyl starch is prepared by including the following components in parts by weight: 60-75 parts of carboxyl starch, 25-40 parts of plasticizer, and 0.05-10 parts of metal salt.
[0011] Furthermore, the carboxyl starch includes at least one of modified Fenton reagent oxidized starch (oxidized starch), maleic anhydride esterified starch, TEMPO oxidized starch, maleic anhydride esterified starch, etc., and is more preferably oxidized starch.
[0012] Furthermore, the plasticizer may be any plasticizer conventionally used in the art, such as at least one of glycerol, ethylene glycol, pentaerythritol, etc., more preferably glycerol.
[0013] Furthermore, the metal salt may include at least one of a soluble zinc salt, a soluble calcium salt, a soluble magnesium salt, and the like.
[0014] Furthermore, the soluble zinc salt may include at least one of zinc acetate, zinc chloride, zinc citrate, zinc tartrate and the like.
[0015] Furthermore, the soluble calcium salt may include at least one of calcium tartrate, calcium chloride, calcium acetate and the like.
[0016] Furthermore, the soluble magnesium salt may include magnesium chloride and the like.
[0017] In the thermoplastic carboxyl starch-based hot melt adhesive of the present invention, the chelated coordinated thermoplastic carboxyl starch is prepared by the following steps: carboxyl starch, plasticizer and metal salt are uniformly mixed in proportion, placed in an extruder for reaction extrusion molding, cooled and granulated to obtain the chelated coordinated thermoplastic carboxyl starch.
[0018] Furthermore, after being uniformly mixed, the material can be allowed to stand for 8-48 hours before extrusion granulation.
[0019] Furthermore, the extruder used may be a co-rotating parallel twin-screw extruder; the temperature from the feed port to the die of the extruder is 80-140° C., and the screw speed is 50-300 r / min, more preferably 120-150 r / min.
[0020] In the thermoplastic carboxyl starch-based hot melt adhesive of the present invention, the viscosity of the tackifier is preferably 700-1800 cp (150° C.).
[0021] Furthermore, the tackifier may include at least one of rosin resin, hydrogenated rosin resin, etc., and more preferably includes rosin resin.
[0022] Furthermore, the antioxidant can be any conventional antioxidant in the art, such as antioxidant 168, antioxidant 1010, antioxidant 1076, etc., and more preferably includes antioxidant 1010.
[0023] Furthermore, the EVA resin is preferably EVA28400.
[0024] The present invention also provides a method for preparing the thermoplastic carboxyl starch-based hot melt adhesive with intrinsic antibacterial and transesterification characteristics, comprising mixing the components in proportion and placing them in an internal mixer for melt blending, followed by cooling and granulation to obtain the hot melt adhesive.
[0025] Furthermore, the temperature of the internal mixer can be 120-170° C., the rotor speed can be 5-120 r / min, and the internal mixing time can be 5-60 min.
[0026] Furthermore, the temperature of the internal mixer can be 140-150° C., the rotor speed can be 80-120 r / min, and the internal mixing time can be 10-40 min.
[0027] The present invention also provides the use of the thermoplastic carboxyl starch-based hot melt adhesive with intrinsic antibacterial and transesterification characteristics. The thermoplastic carboxyl starch-based hot melt adhesive with intrinsic antibacterial and transesterification characteristics of the present invention exhibits excellent bonding effects on materials such as paper, non-woven fabrics, and metals, has high bonding strength, and can be used in the fields of furniture, food, packaging, papermaking, sanitary products, etc.
[0028] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0029] (1) In the hot melt adhesive of the present invention, the chelated coordinated thermoplastic carboxyl starch is used as the matrix and is combined with only a small amount of EVA resin to prepare a thermoplastic carboxyl starch-based hot melt adhesive with excellent intrinsic antibacterial and ester exchange characteristics.
[0030] (2) In the hot melt adhesive of the present invention, the carboxyl starch contains rich carboxyl groups, which changes the ionization balance of bacterial cells, destroys the bacterial expression and physiological activities of bacteria and inhibits their growth and reproduction, thereby showing excellent intrinsic antibacterial properties. Carboxyl starch as a hot melt adhesive matrix can broaden the application scenarios of thermoplastic starch-based hot melt adhesives and extend their service life.
[0031] (3) In the hot melt adhesive of the present invention, the affinity with the metal can be greatly improved through the chelation coordination of the carboxyl group and the metal bonding interface, thereby further improving the bonding performance of the thermoplastic carboxyl starch-based hot melt adhesive to the metal substrate. In addition, the molecular weight of the carboxyl starch can be regulated during the preparation process to achieve a controllable decrease in the molecular weight and an increase in the dispersibility index, which is beneficial to improving the effective penetration and bonding of the thermoplastic carboxyl starch-based hot melt adhesive to the bonding interface.
[0032] (4) In the hot melt adhesive of the present invention, the carboxyl starch can further undergo an ester exchange reaction between the carboxyl group and the ester group with a polyester such as EVA under the catalysis of a metal salt, thereby promoting efficient penetration and fusion of the interface between the two phases, thereby significantly reducing the defect points of the bonding matrix and achieving uniformity of the bonding interface and stability of the interface layer.
[0033] (5) In the hot melt adhesive of the present invention, the coordination effect of carboxyl starch and metal salt can give the thermoplastic carboxyl starch-based hot melt adhesive a temperature-sensitive reversible property. Through the high-temperature dissociation and room-temperature reorganization characteristics of chelation coordination, the adhesive has good fluidity at high temperature and high matrix strength at room temperature. In addition, the chelation coordination structure can also effectively reduce the penetration of water into the matrix, greatly extending the service life of the thermoplastic carboxyl starch-based hot melt adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0035] Figure 1 This is a SEM image of the chelated coordinated thermoplastic carboxyl starch-based hot melt adhesive of Example 4 of the present invention.
[0036] Figure 2-Figure 3 The SEM images of the hot melt adhesives prepared in Comparative Example 1 and Comparative Example 2 are shown respectively. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. The materials involved in the following examples can be obtained from commercial channels unless otherwise specified, and the process parameters not specifically noted can be carried out with reference to conventional techniques. The amount of each component is measured in parts by mass and volume, g, mL.
[0038] The EVA resin (brand: EVA28400) in the examples and comparative examples was purchased from Shanghai Haiyu Chemical Co., Ltd.; the rosin resin was purchased from Jinan Fugang Chemical Co., Ltd., with a viscosity of 700-1800 cp (150° C.) and a softening point of 110-120° C.
[0039] Example 1
[0040] 70 parts by mass of carboxyl starch, 30 parts by mass of glycerol and 3 parts by mass of zinc acetate were added to a mixer and mixed evenly. After standing for 24 hours, the mixture was added to a co-rotating twin-screw extruder for reactive extrusion. The temperature from the feed port of the extruder to the die was set to 90-140°C (the temperatures from the feed port of the extruder to each temperature control zone of the die were set to 90°C, 110°C, 130°C, 135°C, 140°C, 140°C, 135°C and 130°C, respectively), the screw speed was 150 r / min, and chelated coordinated thermoplastic carboxyl starch particles were obtained after cooling and granulation.
[0041] 50 parts by mass of chelated coordinated thermoplastic carboxyl starch, 25 parts by mass of EVA resin, 25 parts by mass of rosin resin, and 0.4 parts by mass of antioxidant 1010 were premixed uniformly by mechanical stirring and then added into an internal mixer for melt blending. The temperature of the internal mixer was 150° C. and the rotor speed was 80 r / min. After internal mixing for 10 minutes, the material was discharged, cooled, and granulated to obtain a thermoplastic carboxyl starch-based hot melt adhesive.
[0042] Example 2
[0043] 70 parts by mass of carboxyl starch, 30 parts by mass of glycerol and 3 parts by mass of zinc acetate were added to a mixer and mixed evenly. After standing for 24 hours, the mixture was added to a co-rotating twin-screw extruder for reactive extrusion. The temperature from the feed port of the extruder to the die was set to 90-140°C (the temperatures from the feed port of the extruder to each temperature control zone of the die were set to 90°C, 110°C, 130°C, 135°C, 140°C, 140°C, 135°C and 130°C, respectively), the screw speed was 150 r / min, and chelated coordinated thermoplastic carboxyl starch particles were obtained after cooling and granulation.
[0044] 60 parts by mass of chelated coordinated thermoplastic carboxyl starch, 20 parts by mass of EVA resin, 20 parts by mass of rosin resin, and 0.4 parts by mass of antioxidant 1010 were premixed uniformly by mechanical stirring and then added into an internal mixer for melt blending. The temperature of the internal mixer was 150° C. and the rotor speed was 90 r / min. After internal mixing for 20 minutes, the material was discharged, cooled, and granulated to obtain a thermoplastic carboxyl starch-based hot melt adhesive.
[0045] Example 3
[0046] 70 parts by mass of carboxyl starch, 30 parts by mass of glycerol and 3 parts by mass of zinc acetate were added to a mixer and mixed evenly. After standing for 24 hours, the mixture was added to a co-rotating twin-screw extruder for reactive extrusion. The temperature from the feed port of the extruder to the die was set to 90-140°C (the temperatures from the feed port of the extruder to each temperature control zone of the die were set to 90°C, 110°C, 130°C, 135°C, 140°C, 140°C, 135°C and 130°C, respectively), the screw speed was 150 r / min, and chelated coordinated thermoplastic carboxyl starch particles were obtained after cooling and granulation.
[0047] 70 parts by mass of chelated coordinated thermoplastic carboxyl starch, 15 parts by mass of EVA resin, 15 parts by mass of rosin resin, and 0.4 parts by mass of antioxidant 1010 were premixed mechanically and then added into an internal mixer for melt blending. The temperature of the internal mixer was 150°C and the rotor speed was 100 r / min. After mixing for 30 minutes, the material was discharged, cooled, and granulated to obtain a thermoplastic carboxyl starch-based hot melt adhesive sample.
[0048] Example 4
[0049] 70 parts by mass of carboxyl starch, 30 parts by mass of glycerol and 3 parts by mass of zinc acetate were added to a mixer and mixed evenly. After standing for 24 hours, the mixture was added to a co-rotating twin-screw extruder for reactive extrusion. The temperature from the feed port of the extruder to the die was set to 90-140°C (the temperatures from the feed port of the extruder to each temperature control zone of the die were set to 90°C, 110°C, 130°C, 135°C, 140°C, 140°C, 135°C and 130°C, respectively), the screw speed was 150 r / min, and chelated coordinated thermoplastic carboxyl starch particles were obtained after cooling and granulation.
[0050] 80 parts by mass of chelated coordinated thermoplastic carboxyl starch, 10 parts by mass of EVA resin, 10 parts by mass of rosin resin, and 0.4 parts by mass of antioxidant 1010 were premixed uniformly by mechanical stirring and then added into an internal mixer for melt blending. The temperature of the internal mixer was 150°C and the rotor speed was 110 r / min. After internal mixing for 40 minutes, the material was discharged, cooled, and granulated to obtain a thermoplastic carboxyl starch-based hot melt adhesive.
[0051] Example 5
[0052] 70 parts by mass of maleic anhydride esterified starch, 30 parts by mass of glycerol and 3 parts by mass of zinc acetate were added to a mixer and mixed evenly. After standing for 24 hours, the mixture was added to a co-rotating twin-screw extruder for reactive extrusion. The temperature from the feed port of the extruder to the die was set to 90-140°C (the temperatures from the feed port of the extruder to each temperature control zone of the die were set to 90°C, 110°C, 130°C, 135°C, 140°C, 140°C, 135°C and 130°C, respectively), the screw speed was 150 r / min, and chelated coordinated thermoplastic maleic anhydride esterified starch particles were obtained after cooling and granulation.
[0053] 80 parts by weight of chelated coordinated thermoplastic maleic anhydride esterified starch, 10 parts by weight of EVA resin, 10 parts by weight of rosin resin, and 0.4 parts by weight of antioxidant 1010 were premixed uniformly with mechanical stirring and then added into an internal mixer for melt blending. The temperature of the internal mixer was 140°C and the rotor speed was 120 r / min. After internal mixing for 40 minutes, the material was discharged, cooled, and granulated to obtain a thermoplastic maleic anhydride esterified starch-based hot melt adhesive.
[0054] Example 6
[0055] 70 parts by mass of maleic anhydride esterified starch, 30 parts by mass of glycerol and 3 parts by mass of zinc acetate were added into a blender and mixed evenly. After standing for 24 hours, the mixture was added into a co-rotating twin-screw extruder for reaction extrusion. The temperature from the feed port of the extruder to the die was set to 80-130°C (the temperatures from the feed port of the extruder to each temperature control zone of the die were set to 80°C, 100°C, 120°C, 125°C, 130°C, 130°C, 125°C and 120°C, respectively), the screw speed was 120 r / min, and chelated coordinated thermoplastic maleic anhydride esterified starch particles were obtained after cooling and granulation.
[0056] 80 parts by weight of chelated coordinated thermoplastic maleic anhydride esterified starch, 10 parts by weight of EVA resin, 10 parts by weight of rosin resin, and 0.4 parts by weight of antioxidant 1010 were premixed uniformly with mechanical stirring and then added into an internal mixer for melt blending. The temperature of the internal mixer was 140° C. and the rotor speed was 120 r / min. After internal mixing for 40 minutes, the material was discharged, cooled, and granulated to obtain a thermoplastic maleic anhydride esterified starch-based hot melt adhesive.
[0057] Example 7
[0058] 60 parts by mass of carboxyl starch, 40 parts by mass of glycerol and 3 parts by mass of zinc acetate were added to a mixer and mixed evenly. After standing for 24 hours, the mixture was added to a co-rotating twin-screw extruder for reactive extrusion. The temperature from the feed port of the extruder to the die was set to 80-120°C (the temperatures from the feed port of the extruder to each temperature control zone of the die were set to 80°C, 90°C, 110°C, 115°C, 120°C, 120°C, 115°C and 110°C, respectively), the screw speed was 120 r / min, and chelated coordinated thermoplastic carboxyl starch particles were obtained after cooling and granulation.
[0059] 80 parts by mass of chelated coordinated thermoplastic carboxyl starch, 10 parts by mass of EVA resin, 10 parts by mass of rosin resin, and 0.4 parts by mass of antioxidant 1010 were premixed uniformly by mechanical stirring and then added into an internal mixer for melt blending. The temperature of the internal mixer was 140°C and the rotor speed was 120 r / min. After internal mixing for 40 minutes, the material was discharged, cooled, and granulated to obtain a thermoplastic carboxyl starch-based hot melt adhesive sample.
[0060] Example 8
[0061] 75 parts by mass of carboxyl starch, 25 parts by mass of glycerol and 3 parts by mass of zinc acetate were added to a blender and mixed evenly. After standing for 24 hours, the mixture was added to a co-rotating twin-screw extruder for reactive extrusion. The temperature from the feed port of the extruder to the die was set to 90-140°C (the temperatures from the feed port of the extruder to each temperature control zone of the die were set to 90°C, 110°C, 130°C, 135°C, 140°C, 140°C, 135°C and 130°C, respectively), the screw speed was 120 r / min, and chelated coordinated thermoplastic carboxyl starch particles were obtained after cooling and granulation.
[0062] 80 parts by mass of chelated coordinated thermoplastic carboxyl starch, 10 parts by mass of EVA resin, 10 parts by mass of rosin resin, and 0.4 parts by mass of antioxidant 1010 were premixed uniformly by mechanical stirring and then added into an internal mixer for melt blending. The temperature of the internal mixer was 150°C and the rotor speed was 120 r / min. After internal mixing for 40 minutes, the material was discharged, cooled, and granulated to obtain a thermoplastic carboxyl starch-based hot melt adhesive sample.
[0063] Example 9
[0064] 70 parts by mass of carboxyl starch, 30 parts by mass of glycerol and 4 parts by mass of calcium acetate were added to a blender and mixed evenly. After standing for 24 hours, the mixture was added to a co-rotating twin-screw extruder for reactive extrusion. The temperature from the feed port of the extruder to the die was set to 80-130°C (the temperatures from the feed port of the extruder to each temperature control zone of the die were set to 80°C, 100°C, 120°C, 125°C, 130°C, 130°C, 125°C and 120°C, respectively), the screw speed was 120 r / min, and chelated coordinated thermoplastic carboxyl starch particles were obtained after cooling and granulation.
[0065] 80 parts by mass of chelated coordinated thermoplastic carboxyl starch, 10 parts by mass of EVA resin, 10 parts by mass of rosin resin, and 0.4 parts by mass of antioxidant 1010 were premixed uniformly by mechanical stirring and then added into an internal mixer for melt blending. The temperature of the internal mixer was 150°C and the rotor speed was 120 r / min. After internal mixing for 40 minutes, the material was discharged, cooled, and granulated to obtain a thermoplastic carboxyl starch-based hot melt adhesive sample.
[0066] Comparative Example 1
[0067] 70 parts by mass of ordinary corn starch, 30 parts by mass of glycerol and 1 part by mass of malic acid were added to a blender and mixed evenly. After standing for 24 hours, the mixture was added to a co-rotating twin-screw extruder for reactive extrusion. The temperature from the feed port of the extruder to the die was set to 80-130°C (the temperatures from the feed port of the extruder to each temperature control zone of the die were set to 80°C, 100°C, 120°C, 125°C, 130°C, 130°C, 125°C and 120°C, respectively), the screw speed was 120 r / min, and thermoplastic starch was obtained after cooling and granulation.
[0068] 60 parts by mass of thermoplastic starch, 20 parts by mass of EVA resin, 20 parts by mass of rosin resin, and 0.4 parts by mass of antioxidant 1010 were premixed uniformly by mechanical stirring and then added into an internal mixer for melt blending. The temperature of the internal mixer was 150°C and the rotor speed was 120 r / min. After internal mixing for 40 minutes, the material was discharged, cooled, and granulated to obtain a thermoplastic starch-based hot melt adhesive.
[0069] Comparative Example 2
[0070] 70 parts by mass of carboxyl starch and 30 parts by mass of glycerol were added to a blender and mixed evenly. After standing for 24 hours, the mixture was added to a co-rotating twin-screw extruder for reactive extrusion. The temperature from the feed port of the extruder to the die was set to 90-140°C (the temperatures of the temperature control zones from the feed port of the extruder to the die were set to 90°C, 110°C, 130°C, 135°C, 140°C, 140°C, 135°C, and 130°C, respectively), the screw speed was 150 r / min, and after cooling and granulation, thermoplastic carboxyl starch particles without chelating coordination were obtained.
[0071] 80 parts by mass of thermoplastic carboxyl starch without chelating coordination, 10 parts by mass of EVA resin, 10 parts by mass of rosin resin, and 0.4 parts by mass of antioxidant 1010 were mechanically stirred and premixed uniformly, and then added into an internal mixer for melt blending. The temperature of the internal mixer was 150° C. and the rotor speed was 110 r / min. After internal mixing for 40 minutes, the material was discharged, cooled, and granulated to obtain a thermoplastic carboxyl starch-based hot melt adhesive without chelating coordination modification.
[0072] Performance Characterization
[0073] (1) The compatibility of the TPS-based hot melt adhesive prepared in the above example and the EVA hot melt adhesive prepared in Comparative Example 1 was observed using SEM. The results are as follows: Figure 1 , Figure 2 , Figure 3 shown. Figure 1 This is a SEM image of the chelated coordinated thermoplastic carboxyl starch-based hot melt adhesive of Example 4 of the present invention. Figure 2 and Figure 3 The SEM images of the hot melt adhesives prepared in Comparative Example 1 and Comparative Example 2 are shown respectively.
[0074] As can be seen from the figure, the domain of EVA / rosin resin in the hybrid coordinated thermoplastic carboxyl starch in the present invention is smaller than that of the thermoplastic starch / acrylamide grafted starch hot melt adhesive without hybrid coordination, and is basically less than 1 μm. This is because the transesterification between carboxyl starch and EVA under the catalysis of metal salts promotes the dispersion of the resin in the thermoplastic carboxyl starch matrix. This feature will contribute to the uniformity of the bonding matrix and the stability of the bonding interface, thereby greatly improving the matrix strength and bonding strength.
[0075] (2) The antibacterial performance of the hot melt adhesive of the present invention was tested. Experimental operation: The antibacterial performance of the hot melt adhesive sample against Staphylococcus aureus (ATCC6538) and Escherichia coli (ATCC8739) was tested by the inhibition zone method. The specific operation steps are: 100 μL of activated bacterial solution (OD=0.5) was evenly coated on the agar medium and the sample (cut into small discs with a diameter of 8 mm and a thickness of 1 mm) was placed on the surface of the medium. After the sample was placed, the medium was placed in a 37°C cell culture incubator and cultured for 24 hours. After the culture was completed, the diameter of the inhibition zone was measured by the cross method. Taking Comparative Example 1 as the blank, the relative growth rate of the inhibition zone was calculated. The results are shown in Table 1 below.
[0076] Relative growth rate of inhibition zone % = (diameter of inhibition zone of example - diameter of inhibition zone of blank comparison) / diameter of inhibition zone of blank comparison * 100%
[0077] Table 1
[0078]
[0079] As can be seen from the table, the thermoplastic carboxyl starch hot melt adhesive of the present invention has excellent antibacterial effect, and the diameter of the antibacterial zone can reach 45 mm. The hot melt adhesive of the present invention uses carboxylated starch as a matrix, which can change the ionization balance of bacterial cells, destroy bacterial expression and physiological activities of bacteria and inhibit their growth and reproduction, thereby showing excellent intrinsic antibacterial properties.
[0080] (3) The hot melt adhesives prepared in the above Examples 1-9 and Comparative Examples 1-2 were subjected to a copper sheet lap bonding strength test (tested in accordance with GB / T 7124-2008 standard, with a tensile rate of 5 mm / min) and an aluminum tape peel strength test (tested in accordance with GB / T2791-1995 standard, with a tensile rate of 200 mm / min). The test results are shown in Table 2.
[0081] Table 2
[0082]
[0083] As can be seen from the table, compared with the comparative example, the bonding strength of the carboxyl starch-based hot melt adhesive with ester exchange characteristics of the present invention is significantly improved compared with ordinary thermoplastic starch-based hot melt adhesives and metal ion-free carboxyl starch-based hot melt adhesives. The comparison results of Comparative Example 2 and Comparative Example 1 show that carboxyl starch is crucial to improving the bonding strength of hot melt adhesives. This is because the molecular weight of carboxyl starch decreases in a controllable manner during the preparation process of carboxyl starch, the molecular weight distribution becomes wider, and a large number of polar group carboxyl groups are introduced. The rich polar groups and good infiltration of low molecular weight components help the thermoplastic carboxyl starch-based hot melt adhesive to effectively penetrate the bonding interface and improve the interfacial bonding strength. At the same time, the carboxyl group can not only improve the affinity with the bonding interface through double hydrogen bonds, but also improve the cohesive energy density of the hot melt adhesive matrix to prevent cohesive damage of the adhesive layer.
[0084] In addition, through the catalysis of metal salts, carboxyl starch can undergo an ester exchange reaction with the ester bond of EVA, promoting efficient penetration and fusion of the two-phase interface, which will significantly reduce the defect points of the bonding matrix and achieve the uniformity of the bonding interface and the stability of the interface layer. More importantly, the coordination effect of carboxyl starch and metal salts can give thermoplastic carboxyl starch-based hot melt adhesives temperature-sensitive reversible properties. Through the high-temperature dissociation and room-temperature reorganization characteristics of chelation coordination, the good fluidity of the adhesive at high temperature and high matrix strength at room temperature are achieved. In addition, the chelated coordination structure can also effectively reduce the penetration of water into the matrix and greatly extend the service life of thermoplastic carboxyl starch-based hot melt adhesives. In addition, carboxyl starch is rich in carboxyl groups, which can change the ionization balance of bacterial cells, destroy the bacterial expression and physiological activities of bacteria and inhibit their growth and reproduction, thereby showing excellent intrinsic antibacterial properties. Carboxyl starch as a hot melt adhesive matrix can broaden the use scenarios of thermoplastic starch-based hot melt adhesives and extend their service life.
[0085] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A thermoplastic carboxyl starch-based hot melt adhesive with intrinsic antibacterial and transesterification characteristics, characterized in that The method is prepared by comprising the following components in parts by weight: 40-80 parts of chelated coordinated thermoplastic carboxyl starch, 10-30 parts of ethylene-vinyl acetate copolymer, 10-30 parts of tackifier, and 0.2-0.4 parts of antioxidant; The chelated coordinated thermoplastic carboxyl starch is prepared by comprising the following components in parts by weight: 60-75 parts of carboxyl starch, 25-40 parts of plasticizer, and 0.05-10 parts of metal salt.
2. The thermoplastic carboxyl starch-based hot melt adhesive with intrinsic antibacterial and transesterification characteristics according to claim 1, characterized in that: The carboxyl starch includes at least one of modified Fenton reagent oxidized starch, maleic anhydride esterified starch, TEMPO oxidized starch and maleic anhydride esterified starch.
3. The thermoplastic carboxyl starch-based hot melt adhesive with intrinsic antibacterial and transesterification characteristics according to claim 1, characterized in that: The plasticizer includes at least one of glycerol, ethylene glycol and pentaerythritol; the metal salt includes at least one of soluble zinc salt, soluble calcium salt and soluble magnesium salt.
4. The thermoplastic carboxyl starch-based hot melt adhesive with intrinsic antibacterial and transesterification characteristics according to claim 3, characterized in that: The soluble zinc salt includes at least one of zinc acetate, zinc chloride, zinc citrate and zinc tartrate; the soluble calcium salt includes at least one of calcium tartrate, calcium chloride and calcium acetate; and the soluble magnesium salt includes magnesium chloride.
5. The thermoplastic carboxyl starch-based hot melt adhesive with intrinsic antibacterial and transesterification characteristics according to any one of claims 1 to 4, characterized in that The chelated coordinated thermoplastic carboxyl starch is prepared by the following steps: carboxyl starch, plasticizer and metal salt are mixed evenly according to proportion, placed in an extruder for reaction extrusion molding, cooled and granulated to obtain the chelated coordinated thermoplastic carboxyl starch.
6. The thermoplastic carboxyl starch-based hot melt adhesive with intrinsic antibacterial and transesterification characteristics according to claim 5, characterized in that: The temperature from the extruder feed port to the die head is 80-140°C, and the screw speed is 50-300r / min.
7. The thermoplastic carboxyl starch-based hot melt adhesive with intrinsic antibacterial and transesterification characteristics according to any one of claims 1 to 4, characterized in that: The tackifier includes at least one of rosin resin and hydrogenated rosin resin; the antioxidant includes at least one of antioxidant 168, antioxidant 1010, and antioxidant 1076.
8. The method for preparing a thermoplastic carboxyl starch-based hot melt adhesive having intrinsic antibacterial and transesterification characteristics according to any one of claims 1 to 7, characterized in that The method comprises mixing the components in proportion, placing the components in an internal mixer for melting and blending, and then cooling and granulating the components to obtain the product.
9. The method for preparing the thermoplastic carboxyl starch-based hot melt adhesive according to claim 8, characterized in that: The temperature of the internal mixer is 120-170°C, the rotor speed is 5-120r / min, and the internal mixing time is 5-60min.
10. Application of the thermoplastic carboxyl starch-based hot melt adhesive with intrinsic antibacterial and transesterification characteristics as claimed in any one of claims 1 to 7 in the fields of furniture, food, packaging, papermaking and sanitary products.
Citation Information
Patent Citations
A kind of preparation method of rosin / starch base biodegradable hot melt adhesive
CN104312482B
Biodegradable TPS-based hot melt adhesive with high metal bonding strength as well as preparation and application of TPS-based hot melt adhesive
CN114381218A
Antibacterial TPS-based hot melt adhesive with high matrix strength as well as preparation method and application of antibacterial TPS-based hot melt adhesive
CN117165218A
Adhesive composition
JP2010126555A
Method for preparing a modified environment-friendly corn starch adhesive
US20210253917A1